Experimental Investigation on Fly Ash and GGBS Based Geopolymer Concrete Incorporate Black Marble Waste Aggregate - Pradeep Kumar, S; Kameswara Rao, B; Guru Jawahar, J (International Journal of Engineering and Technology, 2018)
In show development area usage of common assets is expanded, this cases to decrease in accessible natural assets. Then again high volume of creation has produced a lot of waste materials which have antagonistic effect on the environment. Natural coarse aggregate is one of the material used in concrete, it causes a shortage in future and causes environmental damage. Several studies have been carried out to reduce the utilization of natural coarse aggregate (NCA) in concrete. There is need to supplementary material like demolished concrete waste aggregate, recycle aggregate, marble and granite aggregates, which are by-products from stone industries. In this experimental work, black marble waste aggregate (BMWA) was used as coarse aggregate at different replacement levels (0%, 50% and 100%) in geopolymer concrete (GPC). The compressive quality of GPC mixes was determined after 28 days of curing and then compared with GPC using natural coarse aggregate.Â Â